Analysis of Students' Errors in Solving the Least Common Multiple and Greatest Common Divisor Word Problems - Ana Puji Lestari; Inti Nahdataeni S (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2022)
Students' ability to solve word problems has an essential role in learning mathematics. However, some junior high school students still have difficulty in solving word problems. The difficulties experienced by students cause errors when solving mathematical word problems. This qualitative study aims to analyze students' errors in solving the Least Common Multiple and Greatest Common Divisor word problems. Fifty-nine students of Integrated Islamic Junior High School Al-Fahmi in Palu were involved in this study. Two students were selected to participate in the interview process. The interview was conducted to obtain in-depth information about how students solve word problems and the types of errors experienced by students. Students' errors in solving word problems were analyzed based on Newman's theory. The errors experienced by students are comprehension errors, transformation errors, process skills errors, and encoding errors